Kecenderungan kenakalan siswa pondok: Bagaimana peran penyesuaian diri? (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2022)
Adolescence is a period of transition from childhood to adulthood. Various changes are experienced at this time, both in terms of physical, cognitive and socio-emotional. Teenagers as students in a school are certainly required to be able to make adjustments to the school environment. Both adjustments to teachers, adjustments to learning methods, adjustments to friends and adjustments to existing norms in the school environment. For this reason, this study aims to determine the relationship between self-adjustment and juvenile delinquency tendencies in Islamic boarding school students by taking 30 population studies sampling on boarding students at Mts. Hasyim Asy'ari. The results of hypothesis testing show a significance value (2-tailed) of 0.000 with a correlation coefficient of -0.698 which indicates that self-adjustment has a significant negative relationship with juvenile delinquency in boarding school students. With a coefficient of determination of 80.1 percent which means that the better the adjustment of the boarding school students, the lower the juvenile delinquency in the boarding school students. The researcher can conclude that there is a very significant negative relationship between self-adjustment and the tendency of juvenile delinquency in boarding school students. which can be interpreted that the better the boarding school students in adjusting, the lower it will be. Masa remaja merupakan masa peralihan dari masa anak menuju masa dewasa. Berbagai perubahan dialami dimasa ini, baik dari segi fisik, kognitif dan sosio-emosional. Remaja sebagai siswa disebuah sekolah tentunya dituntut untuk mampu melakukan penyesuaian terhadap lingkungan sekolah. Baik penyesuaian terhadap guru, penyesuaian terhadap metode pembelajaran, penyesuaian terhadap teman-teman serta penyesuaian terhadap normanorma yang ada di lingkungan sekolah. Untuk itu penelitian ini bertujuan untuk mengetahui hubungan antara penyesuaian diri dengan kecenderungan kenakalan remaja pada siswa Pondok dengan mengambil 30 sampling secara population Studies pada siswa pondok di Mts. Hasyim Asy’ari. Data dikumpulkan menggunakan skala Likert dan dilakukan analisis menggunakan Kolerasi Spearmen. Hasil pengujian hipotesis menunjukkan nilai signifikansi (2-tailed) sebesar 0,000 dengan koefisiensi Korelasi – 0,698 yang menunjukkan bahwa penyesuaian diri memiliki hubungan negatif yang signifikan dengan kenakalan remaja pada siswa pondok. Dengan koefisiensi determinasi sebesar 80,1 persen yang berarti bahwa semakin baik penyesuaian diri siswa pondok maka akan semakin menurun kenakalan remaja pada siswa pondok. Dapat peneliti simpulkan bahwa ada hubungan negatif yang sangat signifikan antara penyesuaian diri dengan kecenderungan kenakalan remaja pada siswa pondok. yang dapat diartikan bahwa semakin baik siswa pondok dalam menyesuaikan diri maka akan semakin rendah.